The last archer - Smith, S. D. (Sam Smith) (Smith, S. D. (Sam Smith). Green ember (Series), 2017)
"A Green Ember story set during Heather and Picket's arrival at Cloud Mountain, The Last Archer follows the journey of Jo Shanks. Jo is a gifted archer with a burden on his back and a fire within. Eager to see the Longtreaders receive justice, he travels from his Halfwind Citadel home to a Cloud Mountain poised on the brink of war. What he finds there will confront his convictions and test his resolve as the war begins and King Jupiter's heir is revealed. A kingdom in the balance. An arrow aimed at the heart of darkness. Who will take the shot?"